1999
DOI: 10.1111/j.1574-6968.1999.tb08837.x
|View full text |Cite
|
Sign up to set email alerts
|

A xylanase produced by the rumen anaerobic protozoanPolyplastron multivesiculatumshows close sequence similarity to family 11 xylanases from Gram-positive bacteria

Abstract: We report for the first time the cloning and characterisation of a protozoal enzyme involved in plant cell wall polysaccharide degradation. A cDNA library was constructed from the ruminal protozoan Polyplastron multivesiculatum and a stable clone expressing xylanase activity was isolated. The encoded enzyme belongs to the glycoside hydrolase family 11, and phylogenetic analysis indicates a closer relationship with catalytic domains from Gram-positive bacteria than the other fibrolytic eukaryotes from the rumen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(8 citation statements)
references
References 23 publications
2
6
0
Order By: Relevance
“…This result agrees with previously published observations that genes acquired by HGT in Actinobacteria mostly originated from beta- and gamma-Proteobacteria [6]. The genes acquired by HGT in fungi [61] and HGT in ciliates such as T. thermophila [26], [62] mostly originated from bacteria. D. discoideum may have transferred the pyr-redox gene to Mycobacterium spp.…”
Section: Discussionsupporting
confidence: 92%
“…This result agrees with previously published observations that genes acquired by HGT in Actinobacteria mostly originated from beta- and gamma-Proteobacteria [6]. The genes acquired by HGT in fungi [61] and HGT in ciliates such as T. thermophila [26], [62] mostly originated from bacteria. D. discoideum may have transferred the pyr-redox gene to Mycobacterium spp.…”
Section: Discussionsupporting
confidence: 92%
“…Some marine algae are also reported to secrete xylanases in extracellular environment (Polizeli et al 2005 ). Xylanases of protozoan and crustacean origin are also reported (Devillard et al 1999 ; Polizeli et al 2005 ). Unusual xylanases from the gut of insects have been studied (Roy et al 2003 ; Brennan et al 2004 ).…”
Section: Introductionmentioning
confidence: 90%
“…Using these techniques we and others have been able to isolate and characterize genes from a range of rumen protozoa ( McEwan et al, 1999 ; Newbold et al, 2005 ; Belzecki et al, 2007 ; Boxma et al, 2007 ). This includes a wide range of fibrolytic enzymes a number of which have been found to contain multiple domains with binding domains and putative chimeric constructs being observed suggesting a highly evolved fibrolytic capacity in the rumen ciliates ( Devillard et al, 1999 , 2003 ; Takenaka et al, 1999 , 2004 ; Wereszka et al, 2004 ; Bera-Maillet et al, 2005 ). This observation has been confirmed by recent metagenomic screening of protozoal glucosidases and eukaryotic metatranscriptomes that have confirmed that a diverse range of diverse glycoside hydrolases are present in the rumen protozoa ( Findley et al, 2011 ; Qi et al, 2011 ).…”
Section: Functional Genes In Rumen Ciliate Protozoamentioning
confidence: 99%